Aspects of psychology in sports medicine. Issue 4 (December 1991) - Greenspan, M; Fitzsimmons, P; Biddle, S
Abstract : Psychology's impact as an ergogenic aid across sports and competitive levels has been well documented. In addition, exercise can play a major role in disease prevention and health enhancement while also enhancing psychological well-being. In addition to its preventive value, exercise is being recognized as a valuable therapeutic tool. Like most therapeutic modalities, however, exercise also has some potentially negative qualities.